Oligoarginine Peptide Conjugated to BSA Improves Cell Penetration of Gold Nanorods and Nanoprisms for Biomedical Applications - Karen Bolaños; Macarena Sánchez-Navarro; Andreas Tapia-Arellano; Ernest Giralt; Marcelo J. Kogan; Eyleen Araya (MDPI AG, 2021)
Gold nanoparticles (AuNPs) have been shown to be outstanding tools for drug delivery and biomedical applications, mainly owing to their colloidal stability, surface chemistry, and photothermal properties. The biocompatibility and stability of nanoparticles can be improved by capping the nanoparticles with endogenous proteins, such as albumin. Notably, protein coating of nanoparticles can interfere with and decrease their cell penetration. Therefore, in the present study, we functionalized albumin with the r8 peptide (All-D, octaarginine) and used it for coating NIR-plasmonic anisotropic gold nanoparticles. Gold nanoprisms (AuNPrs) and gold nanorods (AuNRs) were coated with bovine serum albumin (BSA) previously functionalized using a cell penetrating peptide (CPP) with the r8 sequence (BSA-r8). The effect of the coated and r8-functionalized AuNPs on HeLa cell viability was assessed by the MTS assay, showing a low effect on cell viability after BSA coating. Moreover, the internalization of the nanostructures into HeLa cells was assessed by confocal microscopy and transmission electron microscopy (TEM). As a result, both nanoconstructs showed an improved internalization level after being capped with BSA-r8, in contrast to the BSA-functionalized control, suggesting the predominant role of CPP functionalization in cell internalization. Thus, our results validate both novel nanoconstructs as potential candidates to be coated by endogenous proteins and functionalized with a CPP to optimize cell internalization. In a further approach, coating AuNPs with CPP-functionalized BSA can broaden the possibilities for biomedical applications by combining their optical properties, biocompatibility, and cell-penetration abilities.